Ransom - Ron Howard; Nolte, Brawley; Delroy Lindo; Gary Sinise; Liev Schreiber; Lili Taylor; Rene Russo; Mel Gibson (USA Imagine Entertainment, 1996)
Tom Mullen, rich airline owner, is shocked when his son is kidnapped. He is willing to pay the two million dollar ransom, but the drop goes wrong. So Tom turns the ransom money into a bounty on the head of the kidnapper.
When a rich man's son is kidnapped, he cooperates with the police at first but then tries a unique tactic against the criminals.
Cyril Hume
Language(s): English, Portuguese Subtitle(s): English, Portuguese, Turkish, Icelandic, Hebrew, Greek, Bulgarian, Estonian
Keywords: Crime; Drama; Thriller; Action